2010
DOI: 10.1007/s10646-010-0478-z
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of copper and low pH on antioxidant defenses and biochemical parameters in neotropical fish pacu, Piaractus mesopotamicus (Holmberg, 1887)

Abstract: Copper sulfate is widely used in aquaculture. Exposure to this compound can be harmful to fish, resulting in oxidative metabolism alterations and gill tissue damage. Pacu, Piaractus mesopotamicus, (wt = 43.4 +/- 3.35 g) were distributed in experimental tanks (n = 10; 180 l) and exposed for 48 h to control (without copper addition), 0.4Cu (0.4 mg l(-1)), 0CupH (without copper addition, pH = 5.0) and 0.4CupH (0.4 mg l(-1), pH = 5.0). In liver and red muscle, the superoxide dismutase (SOD) was responsive to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…The pH of most freshwater systems is predominantly determined by or dependent on atmospheric influences, the mineral content of the surrounding rocks, soils and other landforms. It often ranges from 6 to 8, which is ideal for aquatic life [67,68]. pH values ranging between 6.5 and 8.4 are considered acceptable by the SAWQ guidelines for agricultural use.…”
Section: Discussionmentioning
confidence: 99%
“…The pH of most freshwater systems is predominantly determined by or dependent on atmospheric influences, the mineral content of the surrounding rocks, soils and other landforms. It often ranges from 6 to 8, which is ideal for aquatic life [67,68]. pH values ranging between 6.5 and 8.4 are considered acceptable by the SAWQ guidelines for agricultural use.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported a significant production of ROS by copper exposure (Farmen et al 2010;Manzl et al 2004;Nawaz et al 2004;Pourahmad and O'Brien 2000a, b;Puig and Thiele 2002;Sampaio et al 2010;Viarengo et al 1996;Vutukuru et al 2006) beyond reductions in the levels of antioxidant enzymes (Vutukuru et al 2006). Oxidative stress may affect mitochondrial ATP production due to changes in mitochondrial membrane potential (Krumschnabel et al 2005;Manzl et al 2004;Pourahmad and O'Brien 2000a, b;Xiang and Shao 2003) and alter mitochondrial permeability, leading to a complete depletion of ATP by copper (Krumschnabel et al 2005;Pourahmad and O'Brien 2000b).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, metallothionine was established to be an effective biomarker in response to copper at different pH and dissolved O 2 levels. These factors work together more effectively to produce significant disturbances in biomarkers rather than individually [ 135 ]. In the next study, juvenile Salmo gairdneri fish were exposed to 25–400 µg Cu/L for 24 h in a standardized environments of varying water hardness, with alkalinity maintained at a constant Na concentration.…”
Section: Effect Of External Factors On Copper Toxicity In Aquatic mentioning
confidence: 99%